Community perception of sustainable peat swamp ecosystem conservation in Buntoi Village, Kahayan Hilir Sub-District, Central Kalimantan. Issue 1 (November 2021) - Karlina, E; Yeny, I
Abstract: The sustainability of peat swamp ecosystem management requires conservation efforts to prevent the exploitative and destructive utilization of the ecosystem. The real action efforts of conservation activities are closely related to the support from the surrounding peat forest community. The purpose of the study is to determine the level of community perception of peat ecosystem conservation. The method used is quantitative descriptive, with score intervals using the Likert scale. The study results show that respondents' characteristics indicate that respondents' economic value is in line with the length of stay in Buntoi Village. The value of three indicator community perception is in the high and very high categories. The study results show that the knowledge category of peat ecosystem conservation ranges from 948-1368 (high-very high), the response ranges from 1224-1572 (very high), and community attitude scores from 1260-1584 (very high). Respondents who live > 20 years stated that it is very important to carry out conservation activities. Community perception is agreed and very agree towards conservation efforts in the sustainable use of peat ecosystem. They are ready to participate in all forms of activities, both in private and government programs.